2015
DOI: 10.2514/1.j053654
|View full text |Cite
|
Sign up to set email alerts
|

Local Reduced-Order Modeling and Iterative Sampling for Parametric Analyses of Aero-Icing Problems

Abstract: A framework of local reduced-order modeling using machine learning algorithms is presented together with an approach to optimally select the snapshots for strongly nonlinear problems. By using an unsupervised learning algorithm, solutions are grouped into clusters of similar features. The input parameter space is divided into subregions by decision boundaries based on a supervised learning algorithm. Local reduced-order bases are extracted on each cluster, for which the solutions are represented as a linear co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…Instead of a unique global POD basis, several local bases are computed using machine learning tools yielding to more flexible behaviors bringing out a precise delimitation of the physical regimes. One can note that a comparable approach has been used for aero-icing certification [28]. The specificity of the presented method includes the introduction of a feature extraction with a shock sensor, a novel resampling strategy and the application to a aerodynamics case.…”
Section: Local Decomposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of a unique global POD basis, several local bases are computed using machine learning tools yielding to more flexible behaviors bringing out a precise delimitation of the physical regimes. One can note that a comparable approach has been used for aero-icing certification [28]. The specificity of the presented method includes the introduction of a feature extraction with a shock sensor, a novel resampling strategy and the application to a aerodynamics case.…”
Section: Local Decomposition Methodsmentioning
confidence: 99%
“…The choice of the quantity characterizing the physical regimes, on which the clustering is performed, is a question of central importance impacting the quality of the classification. Usually, the unsupervised learning clusters directly the quantity of interest into groups with patterns of small differences [23,24,28]. However, the aim of the clustering in this paper is the physical regime separation and the previous approach can lead to classification error.…”
Section: Physical-based Shock Sensor To Detect Flow Regimesmentioning
confidence: 99%
“…The most interesting features of POD is that it is linear and that, among all linear representations, it is also optimal, since it minimizes the average squared distance between the actual state of the system and its reduced counterpart. POD represents the system as a linear combination of primitives using the linear manifold in the configuration space represented by the data; therefore, it might show limitations when the nonlinearity of the original system is severe [24]. The mathematical treatment of POD is well covered in the literature and will be briefly outlined here following the method of snapshots proposed by Sirovich [29].…”
Section: B Proper Orthogonal Decomposition Via the Methods Of Snapshotsmentioning
confidence: 99%
“…In the area of fixed-wing aerodynamics, early works can be found that address only inviscid flows or two-dimensional problems, whereas more recent publications target more realistic three-dimensional geometries and viscous turbulent flows. Nonintrusive approaches are more popular when it comes to optimization, parametric analyses, and flow control [21,22]; whereas intrusive methods appear more frequently in the context of aeroelastic studies [23,24]. In the area of helicopter aerodynamics, the use of modal ROMs is not very well documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This might happen when relying for example on Proper Orthogonal Decomposition (POD) (Weller, Lombardi and Iollo 2009;Cazemier 1998) to identify the RBM modes. POD was introduced for the analysis of turbulent flows by Lumley (Lumley 1967) and it has been widely used in literature for both steady and unsteady problems (Stabile and Rozza 2018;Ripepi et al 2018;Stabile et al 2017;Ripepi and Goertz 2015;Zhan, Habashi and Fossati 2015;Iuliano and Quagliarella 2013;Carlberg and Farhat 2008;Lieu, Farhat and Lesoinne 2005;Bui-Thanh 2003;Legresley and Alonso 2000), since it allows to describe most of the information of the initial data set with the lowest number of modes possible (Holmes et al 2012). It identifies a basis, which is the closest to the set of snapshots in terms of an average projection error based on an energy norm.…”
Section: Introductionmentioning
confidence: 99%